Validation of the rapid fluorescent focus inhibition test (RFFIT) for rabies virus neutralizing antibodies in clinical samples - Kostense, Stefan; Moore, Susan M.; Companjen, Arjen; Bakker, Alexander B. H.; Marissen, Wilfred E.; von Eyben, Rie; Weverling, Gerrit Jan; Hanlon, Cathleen A.; Goudsmit, Jaap (My University, 2012)
Monoclonal antibodies are successful biologics in treating a variety of diseases, including the prevention or treatment of viral infections. CL184 is a 1:1 combination of two human monoclonal IgG1 antibodies (CR57 and CR4098) against rabies virus, produced in the PER.C6 human cell line. The two antibodies are developed as replacements of human rabies immune globulin (HRIG) and equine rabies immune globulin (ERIG) in postexposure prophylaxis (PEP). The rapid fluorescent focus inhibition test (RFFIT) is a cell-based virus neutralization assay which is usually performed to determine the biological potency of a vaccine and to measure the levels of protection against rabies in humans and animals. In order to confirm the suitability of this assay as a pharmacodynamic assay, we conducted a validation using both HRIG- and CL184-spiked serum samples and sera from vaccinated donors. The validation results met all analytical acceptance criteria and showed that HRIG and CL184 serum concentrations can be compared. Stability experiments showed that serum samples were stable in various suboptimal conditions but that rabies virus should be handled swiftly once thawed. We concluded that the assay is suitable for the measurement of polyclonal and monoclonal rabies neutralizing antibodies in clinical serum samples.
Keywords: RFFIT; RVNA; Rabies virus; Monoclonal antibodies; HRIG; Validation